A history of Russian philosophy : from the tenth through the twentieth centuries - Kuvakin, Valery A. 1939- (Prometheus Books, 1994)
For the first time since the break up of the USSR, and with the help of 21 leading historians of Russian philosophy from Moscow State University including M. N. Gromov, Z. A. Kamensky, M. A. Maslin, B. G. Safronov, and V. V. Serbinenko, Valery A. Kuvakin presents a comprehensive two-volume work capturing the rich philosophical heritage of this diverse culture. These scholars discuss its interpretation of the universe, the essence of history and human existence, the ideals of knowledge and a decent life, the destiny of Russia, and the life of the world community from the 10th century through the early 20th century. These discussions are augmented with selected excerpts from original works, which served as examples of the main schools of thought.